Związek struktury kapitału z wynikami finansowymi - Wrońska, Elżbieta (Relationship between Capital Structure and Financial Effects, 2006)
This article referes to relationship between capital structure and profit. The capital structure is define as a mixture of debt and equity. The amount of debt and the proportion of debt and equity affect the interests payments. The profits can be measured by net income, economic value added (EVA) or free cash flow to equity (FCFE). The level of profits calculated by every of these measures depends directly on the cost of debt and interests payments. Every measure includes the cost of debt. On the other hand, the amount of debt depends on the level of operating income. The financial leverage has positive effect while high level of operating income is gained. The higher level of operating income is needed to take advantage of financial leverage when using EVA or FCFE as measures of profit. It means that when using net income as a measure of profit lower level of operating income to gain positive effects of financial leverage is needed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 726-736